Marker of coxsackievirus‐B4 infection in saliva of patients with type 1 diabetes. Issue 7 (30th August 2017) - Badia‐Boungou, F.; Sane, F.; Alidjinou, E.K.; Ternois, M.; Opoko, P.A.; Haddad, J.; Stukens, C.; Lefevre, C.; Gueorguieva, I.; Hamze, M.; Ismail, M.; Weill, J.; et al.
Abstract: Background: Coxsackieviruses B (CV‐B) are enteroviruses that have been reported to play a role in the pathogenesis of type 1 diabetes. Enteroviral RNA was detected in the gut mucosa of patients. The mucosal immunity is an interconnected network; therefore, the response to enteroviruses possibly present in the gastrointestinal mucosa can be reflected by specific antibodies in the saliva. In the present study, the anti‐CV‐B neutralizing activity of saliva samples from patients with type 1 diabetes was investigated. Methods: Saliva samples were collected from patients and controls of 3 countries, and plasma was obtained from some of them. The anti‐CV‐B activity of clinical samples was determined by neutralization of the cytopathic effect induced by challenging viruses in vitro and expressed as titre value. Results: Overall prevalence and levels of anti‐CV‐B4 activity of saliva were higher in patients ( n  = 181) than in controls ( n  = 135; P  = .0002; titre values ≥ 16: odds ratio = 4.22 95% CI: 1.90‐9.38 P  = .0002). It has been shown that IgA1 played a role in this activity. There was no correlation between the saliva and the plasma anti‐CV‐B4 neutralizing activity. The neutralizing activity of saliva against CV‐B1, CV‐B2, CV‐B3, and CV‐B5 existed rarely, if at all. Increased levels of anti‐CV‐B4 activity were observed all along a 4 year follow‐up period in patients but not in matched controls ( P  = .01). Conclusion: There is an anti‐CV‐B4 activity in saliva of patients with type 1 diabetes that may be a useful marker to study the role of CV‐B in the pathogenesis of the disease.